Analysis of the Relationship between Intellectual Capital and Firm Performance: The Moderating Effects of Big 4 Auditors and Group Affiliation - Riki Ronaldo Siringo-Ringo; Riris Rotua Sitorus (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the influence of intellectual capital on firm performance in the financial services sector listed on the Indonesia Stock Exchange for the 2015–2019 period. Methodology: Intellectual capital is measured using the Modified Value Added Intellectual Coefficient (MVAIC) approach, while firm performance is proxied by Return on Assets (ROA) and Tobin’s Q. This study also examines the moderating roles of group affiliation and Big 4 auditors, including moderated moderation testing. The research sample consists of 78 companies with a total of 390 observations, analyzed using a fixed effects panel data regression model with robust standard errors. Findings: The results show that intellectual capital has a positive and significant effect on ROA but no significant effect on Tobin’s Q. Group affiliation is proven to weaken the relationship between intellectual capital and profitability, while Big 4 audits strengthen this relationship. However, the three-way interaction effect shows no statistical significance. These findings emphasize the importance of managing intellectual capital in enhancing the internal financial performance of financial service companies in Indonesia.